The Value Relevance of the Financial Statements’ Information: The Moderating Role of the Board of Directors - Tahat, Effat; Al-Mawali, Hamzah; Tahat, Yasean (Jordan Journal of Business Administration, 2021)
This study aims to examine the direct relationship between a firm’s financial statements’ information and its share price and test the moderating role of the board of directors in this relationship. The sample of this study includes the Jordanian firms listed in the Amman Stock Exchange in the services and manufacturing sectors (non-financial firms) over the period 2012–2016. The data was hand-collected from the companies’ annual reports. Quantitative methodology based on Ohlson’s (1995) valuation model was used for empirical analysis. The results of this examination indicate that investors consider accounting information when making investment decisions. In addition, the findings show that corporate governance mechanisms as a moderator (e.g., board size) can enhance the value relevance of accounting information. Moreover, the findings show that accounting measures can explain variations in a firms’ market value over time. The current study provides some policy implications for various stakeholders, including Jordanian investors and regulators, firms’ boards of directors and accounting regulators (e.g., IASB). Finally, some suggestions for future research have been provided based on the limitations of this study.